Mobile & social game design : monetization methods and mechanics - Fields, Tim (CRC Press, Taylor & Francis Group, 2014)
IntroductionThe Changing TideWhat This Book Is NotWhat Is a Social Game? Are Mobile Games Social? Meet Your CompetitionBBS Games and MUDsMMOsJust Being Multiplayer Doesn't Make You SocialGreat Mobile Games ARE SocialInterview with Words with Friends Creators, The BettnersHistory of Game MonetizationWhat Do We Mean By MonetizationA Brief History of Game MonetizationInterview with Richard Garriott, ""The Three Grand Eras of Gaming""Why Create a Social or Mobile Game?Social and Mobile Games Put a Lot of Power in the Hands of the DevelopersSocial Games Make the Developer ResponsibleSocial Games Gi.